Pengaruh Stress Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan pada PT. Semen Indonesia (Persero) Unit Tonasa Kabupaten Pangkep - Muhammad Yusry Mahendra; Abdi Akbar; Ikhwan Maulana Haeruddin; Romansyah Sahabuddin; Burhanuddin (PT Maju Malaqbi Makkarana, 2023)
This study aims to (1) determine the effect of work stress on employee performance, (2) determine job satisfaction on employee performance, (3) determine work stress and job satisfaction jointly affect employee performance at PT. Semen Indonesia (Persero) Tonasa Unit, Pangkep Regency. The population of this research is all employees, especially supervisors, totaling 310 people. And the sample in this study were 175 people. Data collection techniques were carried out by distributing questionnaires. The data analysis technique used is multiple linear analysis using Statistical Product Service Solution (SPSS). The results of this study indicate that there is a Negative and Significant Influence between Work Stress (X1) and a Positive and Significant Influence between Job Satisfaction (X2) on Employee Performance (Y).